THE EFFECT OF MOBILE SAMSAT SERVICES, E-SAMSAT, AND TAX AMNESTY ON THE REALIZATION OF MOTOR VEHICLE TAX REVENUE IN ENDE REGENCY - Kesia Djami; Herly Oematan; Olivia Tomasowa (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
This study aims to determine the effect of Mobile Samsat services, E-Samsat, and Tax Amnesty on Motor Vehicle Tax (PKB) Revenue in Ende Regency. This study uses a quantitative approach with a causal associative research method. The data used were secondary data in the form of PKB realization reports, Mobile Samsat service data, revenue realization data through E-Samsat, and Tax Amnesty data obtained from the Ende Regency SAMSAT Office for the 2022–2025 period. The data analysis technique used was multiple linear regression analysis with the assistance of SPSS version 26. The results showed that Mobile Samsat partially influenced PKB revenue realization, E-Samsat had no effect on PKB revenue realization, and Tax Amnesty did influence PKB revenue realization. Simultaneously, Mobile Samsat, E-Samsat, and Tax Amnesty influenced Motor Vehicle Tax Revenue Realization in Ende Regency, while other factors were outside this research.